2005
DOI: 10.1007/s00406-005-0605-7
|View full text |Cite
|
Sign up to set email alerts
|

A check on the memory deficit hypothesis of obsessive–compulsive checking

Abstract: A number of recent studies have challenged the hypothesis that patients with obsessive-compulsive disorder (OCD) display global memory deficits. An alleviated form of the memory deficit hypothesis posits that OCD patients share deficits to vividly recall memory episodes. According to the latter view, checking rituals can be understood as counter-productive coping strategies to "enrich" memory episodes in order to make them more distinctive. A source memory task was administered to 27 OCD (17 checkers) and 51 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 38 publications
1
22
0
1
Order By: Relevance
“…Traditional studies of metacognition using questionnaires 11,14,2125 or subjective confidence ratings 10,12,13,15 are subject to influences that may mimic a metacognitive impairment, such as systematic response biases in questionnaires and other confidence scales 26 . Here, we operationalize metacognition as the objective sensitivity of confidence ratings to discrimination performance, as defined by signal detection theory 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Traditional studies of metacognition using questionnaires 11,14,2125 or subjective confidence ratings 10,12,13,15 are subject to influences that may mimic a metacognitive impairment, such as systematic response biases in questionnaires and other confidence scales 26 . Here, we operationalize metacognition as the objective sensitivity of confidence ratings to discrimination performance, as defined by signal detection theory 27 .…”
Section: Introductionmentioning
confidence: 99%
“…An early memory deficit theory of OCD sought to explain pathological doubt and checking rituals by low memory accuracy (Sher, Frost, Kushner, Crews, & Alexander, 1989;Sher, Frost, & Otto, 1983). This model conceptualized obsessive-compulsive pathology as a consequence of preexisting memory problems but the theory has failed to find consistent empirical support (Moritz, Jacobsen, Willenborg, Jelinek, & Fricke, 2006;Tallis, Pratt, & Jamani, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Though there are many points of controversy in the field, one question that leads to spirited debate is whether OCD patients have memory deficits when compared to healthy controls. In addition, memory deficiencies have been proposed as an explanatory model for how checking compulsions in a particular subtype of OCD might develop (Harkin & Kessler, 2011; Jaafari et al, 2013; Moritz, Jacobsen, Willenborg, Jelinek, & Fricke, 2006). …”
Section: Introductionmentioning
confidence: 99%
“…A classic example of a checking compulsion is repeatedly checking the door to make sure it has been locked properly; the corresponding obsession is the intrusive fear that the front door was not properly locked and harm will therefore come to one’s family. In the subgroup of OCD patients with predominant checking compulsions, it has been suggested that working memory deficits may play an etiological role in the generation of repetitive checking behavior (Jaafari et al, 2013; Moritz et al, 2006). In this explanatory model, OCD patients would literally not remember if they had checked the door lock properly, and would therefore need to repeat the behavior until they could retain the memory of locking the door.…”
Section: Introductionmentioning
confidence: 99%